Transfer Pricing Decisions: Tax Income, Exchange Rate, Tunneling Incentive and Multinationality - Ismi Raihan Nadhira; Ardan Gani Asalam (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
Transfer pricing can be misapplied by the company by transferring taxable income to subsidiaries and companies with special relationships to significantly push down the tax expense. This research aims to determine factors that can affect transfer pricing decisions. Those factors include tax income, exchange rates, tunnelling incentives, and multinationals. The research object of this research is a company from the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The samples are eight companies selected with purposive sampling technique, resulting in 40 observation data. The analysis technique implemented in this research is panel data regression tested Eviews12. This research reveals that tax income and tunnelling incentives negatively influence transfer pricing decisions. At the same time, the exchange rate and multi-nationality do not affect transfer pricing decisions. Variable tax income, exchange rate, tunnelling incentives, and multinationals have simultaneously affected transfer pricing decisions.